A novel monoclonal antibody against human thymic stromal lymphopoietin for the treatment of TSLP-mediated diseases - Shi, Lihua; Yu, Mingcan; Jin, Ying; Chen, Peng; Mu, Guangmao; Tam, Susan H.; Cho, Minseon; Tornetta, Mark; Han, Chao; Fung, Man-Cheong; Chiu, Mark L.; Zhang, Di (Frontiers in Immunology, 2024)
IntroductionThymic stromal lymphopoietin (TSLP) is a master regulator of allergic inflammation against pathogens at barrier surfaces of the lung, skin, and gut. However, aberrant TSLP activity is implicated in various allergic, chronic inflammation and autoimmune diseases and cancers. Biologics drugs neutralizing excess TSLP activity represented by tezepelumab have been approved for severe asthma and are being evaluated for the treatments of other TSLP-mediated diseases.Methods and resultsIn this study, we discovered and characterized a novel humanized anti-TSLP antibody TAVO101 with high binding affinity to human TSLP, which blocks TSLP binding to its receptor complexes on cell surface. TAVO101 showed potent neutralization of TSLP activities in the TSLP-driven STAT5 reporter assay and cell proliferation assay. Results from ex vivo studies showed that TAVO101 neutralized TSLP-mediated CCL17 release from primary human CD1c+ dendritic cells and proliferation of activated CD4+ T cells. In addition, TAVO101 showed strong efficacy in both TSLP/OVA-induced asthma and imiquimod induced psoriasis models in hTSLP/hTSLPR double knock-in mice. We further conducted Fc engineering to optimize TAVO101 antibody with reduced affinity to Fcγ receptors and C1q protein but with increased affinity to FcRn receptor for half-life extension.DiscussionBy recognizing a different epitope, similarly potent neutralization of TSLP activities, and longer circulating half-life than tezepelumab, novel anti-TSLP antibody TAVO101 offers a potential best-in class therapeutics for various TSLP-mediated diseases.